1989
DOI: 10.1590/s0036-46651989000200003
|View full text |Cite
|
Sign up to set email alerts
|

Soroepidemiologia retrospectiva dO HIV-1

Abstract: Amostras de soro de grupos populacionais dos Estados do Pará e Goiás, coletados entre 1974 e 1980, foram testadas (ELISA, imunofluorescência e immunoblot) para a presença de anticorpos contra o vírus da imunodeficiência humana tipo-1 (HIV-1). O objetivo principal foi de se mapear epidemiologicamente a ocorrência deste vírus em um período anterior a detecção da presente epidemia. Quatro amostras dos índios Xicrin foram positivas pelo teste de ELISA, porém não foram confirmadas pelos demais testes. Os resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The rationale was to investigate groups vulnerable to the acquisition of other STIs, that could already be hosting the virus, and indigenous communities that could provide answers about the ancestry of the infection. There was no evidence of HIV-1 infection, showing that spread of the virus probably did not precede the first cases recorded in Brazil [ 28 ]. Clinical and epidemiological information on viral infection were generated by other laboratories [ 29 ] located in the Brazilian Amazon and it became evident that the epicenter of the epidemic had been the southeast region and the virus rapidly spread to all other regions, including the Amazon region [ 30 ].…”
Section: The Impact Of Hiv-1 In the Brazilian Amazon: From Description To Current Timesmentioning
confidence: 99%
“…The rationale was to investigate groups vulnerable to the acquisition of other STIs, that could already be hosting the virus, and indigenous communities that could provide answers about the ancestry of the infection. There was no evidence of HIV-1 infection, showing that spread of the virus probably did not precede the first cases recorded in Brazil [ 28 ]. Clinical and epidemiological information on viral infection were generated by other laboratories [ 29 ] located in the Brazilian Amazon and it became evident that the epicenter of the epidemic had been the southeast region and the virus rapidly spread to all other regions, including the Amazon region [ 30 ].…”
Section: The Impact Of Hiv-1 In the Brazilian Amazon: From Description To Current Timesmentioning
confidence: 99%
“…A situation which was shown to be even more critical and distressing was shown by our laboratory concerning the recent entry of HIV-1 within an Indian community, the Tiryio, who reside in the North region of the Amazon. Retrospective seroepidemiology with historical samples from different Indian communities showed that the virus was not present until the early 1990s ( Ishak et al, 1989 ; Zaninovic et al, 1994 ; Machado et al, 2006 ), but it was readily introduced most probably as a sexually transmitted infection ( Machado et al, 2006 ) as usually seen with other viruses and bacteria regarding native Indian communities ( Ishak and Ishak, 2001 ; Machado et al, 2006 ). These are common examples of the entry and spreading of infectious agents affecting previously epidemiologically closed and isolated Indian groups, threatened by sexually transmitted viruses and bacteria that can act as real dangers to their fertility and life span.…”
Section: Introductionmentioning
confidence: 99%